2022
DOI: 10.1101/2022.10.17.512624
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The faculty-to-faculty mentorship experience: a survey on challenges and recommendations for improvements

Abstract: Faculty at research institutions play a central role in advancing knowledge and careers, as well as promoting the well-being of students and colleagues in research environments. Faculty members must balance a host of activities - such as performing research, teaching, sourcing funds, administrative and service duties - with their roles as educators and mentors. Mentorship from experienced peers has been touted as critical for enabling these myriad roles to allow faculty development, career progression, and sat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Our study found that minority students who did not work with an advisor of the same demographic, but nevertheless rated their advisor highly on empathy, felt as supported and productive as students whose advisors were a closer demographic match. Beyond simply 'empathy', this may encompass allocating time and funding equitably within their labs, tailoring their mentoring strategy to each student's needs, modeling ethical behavior, welcoming honest feedback without fear of repercussions, and advocating for institutional change that supports the needs of underrepresented students (13,14,16,30,31).…”
Section: Representation By Advisorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found that minority students who did not work with an advisor of the same demographic, but nevertheless rated their advisor highly on empathy, felt as supported and productive as students whose advisors were a closer demographic match. Beyond simply 'empathy', this may encompass allocating time and funding equitably within their labs, tailoring their mentoring strategy to each student's needs, modeling ethical behavior, welcoming honest feedback without fear of repercussions, and advocating for institutional change that supports the needs of underrepresented students (13,14,16,30,31).…”
Section: Representation By Advisorsmentioning
confidence: 99%
“…In science education, doctoral advising is a major component of the so-called "leaky pipeline" by which students from minority backgrounds leave science. Graduate students from minority backgrounds frequently report less support from their advisors and departments (9)(10)(11)(12)(13). These differences in mentoring experiences likely exacerbate existing disparities in the composition of students aspiring to and attaining scientific careers (10,12).…”
Section: Introductionmentioning
confidence: 99%
“…Mentoring, defined as a professional relationship between two people where the mentor provides advice and guidance to their mentee to help them grow, learn, and develop professionally, has been strongly attributed and recognized for its role in organizational performance (Reeves, 2023;Hill et al, 2022;Xu et al, 2021). In the context of universities, mentoring not only aids in the personal and professional development of faculty members but also significantly impacts the overall performance of the institution (Sarabipour et al, 2023).…”
Section: Introductionmentioning
confidence: 99%